Przygraniczna współpraca powiatów województwa warmińsko-mazurskiego z Obwodem Kaliningradzkim FR - Zabielska, Izabela; Koszyk-Białobrzeska, Renata (Border Co-Operation of Districts of Warmia and Mazury Voivodship and Kaliningrad Oblast of the Russian Federation, 2009)
The Kaliningrad Oblast of the Russian Federation is an important area for Warmia and Mazury voivodship from the geopolitical and geo-economic perspective. Cross-border co-operation is becoming important in both bilateral and multilateral dimension considering the European and Euro-Atlantic integration processes. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 895-902